Pengaruh Perilaku Kewirausahaan Dan Modal Usaha Terhadap Keberhasilan Usaha Di Kecamatan Telanaipura Kota Jambi - Nisa Gistia Ningsih; Anzu Elvia Zahara; Puteri Anggi Lubis (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Entrepreneurial behavior and capital are interrelated and complementary in the context of business success. Entrepreneurship brings ideas and vision, while capital provides the financial impetus to turn those ideas into reality. The success of a business is determined by how these two elements integrate and are effectively managed by entrepreneurs. Therefore, a good understanding of entrepreneurship and the importance of capital will assist entrepreneurs in facing challenges and building sustainable and successful businesses. This research aims to determine the influence of entrepreneurial behavior and capital on business success in Telanaipura District, Jambi City. The method used in this study is quantitative research with data analysis using the coefficient of determination test. The sample in this study consisted of 30 respondents who are coffee shop/cafeteria owners in Telanaipura District, Jambi City. The results of the study indicate that entrepreneurial behavior has a positive and significant partial influence on business success, while capital does not have a positive and significant influence on business success. Simultaneously, the results show that entrepreneurial behavior and capital together have a significant influence on business success in Telanaipura District, Jambi City. The coefficient of determination calculations shows that the entrepreneurial behavior variable accounts for 37.5% of the variance, while the remaining 62.5% is influenced by other variables outside the scope of this study.